My nine book - Moncure, Jane Belk (Elgin, Ill : The Child's World, Inc, 1985)
Little Nine introduces the concept of "nine" by interacting with nine of a variety of things which group and regroup to demonstrate principles of adding and subtracting.
Keywords: Nine (The Number) -- Juvenile literature; Number concept; Counting